The Cambridge companion to twenty-first-century American poetry - Yu, Timothy (Professor of literature) (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"The Cambridge Companion to Twenty-First Century American Poetry offers a comprehensive introduction to studying the diversity of American poetry in the current century. While having important continuities with the poetry of the previous century, twenty-first-century poetry takes place in new modes and contexts that require new critical paradigms. This collection highlights the new, multiple centers of gravity that characterize American poetry today. Essays on African American, Asian American, Latinx, and Native American poetries respond to the centrality of issues of race and indigeneity in contemporary American discourse. Other essays explore poetry and feminism, poetry and disability, and queer poetics. The environment, capitalism, and war emerge as poetic preoccupations, alongside a range of styles from spoken word to the avant-garde, and an examination of poetry's place in the creative writing era"--
Includes bibliographical references and index.
Keywords: American poetry -- 21st century